PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII5 SMP NEGERI 6 PEKANBARU - Arifin, Jefani; ', Zulkarnain; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research is student of class VIII5 SMPN 6 Pekanbaru in academic years 2016/2017, which amounted to 33 students, consist of 13 boys and 20 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced  and  actived in learning process, such as while they were finished mathemathic’s problems that given,  presenting the result of  problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (48,48%) to the first test (72,73%)  to the second test II (87,88%). For the skills of basic score (54,55%) to the first test (72,73%) to the second test (84,85%), for the attitude of the basic score (93,94%) for the first cycle (96,97 %) to the second cycle (100%). Results of this research indicates that appication of the learning model of Problem Based Learning can improve learning process and increase mathematics achievement from the students at class VIII5 SMPN 6 Pekanbaru in academic years 2016/2017 for the subject matter algebra operations and functions.